THE EFFECTIVENESS OF SCHOOL ACTIVITIES IN THE FORMATION OF STUDENT DISCIPLINE CHARACTERS IN MADRASAH TSANAWIYAH RIYADHATHUL JANNAH VILLAGE SIALANG PANJANG INDRAGIRI HILIR DISTRICT - Muhammad Arasy (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
School is one place that can shape the character of students. In shaping the character of these students, of course all elements of this school must collaborate and take responsibility for the learning objectives themselves, especially the purpose of forming the character of students. Scout activities are activities that contain a lot of character values, character formation apart from learning in class as well as scout activities. This study aims to determine the activities of scouting in the formation of student discipline character in MTs Riyadhatul Jannah, Sialang Panjang Village. This research uses a descriptive qualitative approach. In obtaining data researchers used interview, observation, and documentation methods. Data analysis in this study includes data reduction, data presentation, and drawing conclusions. Checking the validity of the data uses the researcher's diligence and triangulation of data sources. The research stages in this study include the pre-field stage, the stage of field work, the stage of data analysis and the stage of report writing. The results of this study concluded that: 1) Scout activities in the formation of student discipline character at MTs Riyadhatul Jannah have been going as expected. 2) the effectiveness of Scouting activities in establishing students' discipline character in MTs Riyadhatul Jannah can be declared effective, although there are still students who come late to school and practice scouting because of illness or rain, besides that it is also obtained from the results of effectiveness measures namely, accuracy of program targets, and monitoring program. 3) and the visible impact of scouting activities such as Discipline in keeping with the schedule of lessons, discipline in dealing with the temptation to delay time, and self-discipline focuses on student self-reliance.